Inteligência de negócios, fluxo informacional e comunicação: análise dos conteúdos Web sobre a prática de inteligência de negócios em contraponto às produções acadêmicas - Rocha, Anelise Souza (2022)
This research aims to analyze the concept of business intelligence, evaluating the nonsense of practical application, with academic productions, since the main concept of the term is 'umbrella', which provides different definitions for different applications, converging between practice and theory. For this, the content generated on blogs and websites that are in line with practice will be analyzed. Seeking the academic view of the term, the journals published on the CAPES website and the theses and dissertations published in the BDTD (Digital Library of Theses and Dissertations) on the subject will be analyzed. Identifying differences and similarities, for collaboration of the informational and communicational flow, in the practical application and in the studies on the theme, providing a dissemination of information in a coherent way.